2015
DOI: 10.1007/s11255-015-0988-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of continuous positive airway pressure (CPAP) on the respiratory capacity of chronic kidney disease patients under hemodialysis treatment

Abstract: The introduction of a CPAP protocol during hemodialysis sessions had a positive impact on pulmonary function and physical capacity in CKD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Exercise protocols are usually developed in outpatient or in-hospital setting [1113] with the most recent studies recommending that they should be performed during hemodialysis sessions [1416]. Although improvement in physical fitness is expected in response to standardized aerobic activity, data correlating the changes obtained by a protocol that uses a cycle ergometer in respiratory function and functional capacity of patients undergoing hemodialysis are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise protocols are usually developed in outpatient or in-hospital setting [1113] with the most recent studies recommending that they should be performed during hemodialysis sessions [1416]. Although improvement in physical fitness is expected in response to standardized aerobic activity, data correlating the changes obtained by a protocol that uses a cycle ergometer in respiratory function and functional capacity of patients undergoing hemodialysis are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The functioning changes of individuals with CKD undergoing dialysis treatment can also be explained by the changes in volumetric components and the impaired ventilatory capacity that are common in these individuals, as detected in pulmonary function tests [7,8]. The reduction in the strength and endurance of the respiratory muscles, likely due to uremic myopathy [8], is probably another cause of disability.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a similar number of women and men was observed in the groups. This is different from some epidemiological and systematic review studies emphasizing the increased incidence of CKD in women [2,5,13]. Instead, the sample of patients from a public hospital in this study had a homogeneous sex distribution, with equal benefits of exercising for men and women.…”
Section: Discussionmentioning
confidence: 68%
“…As our study progressed, we observed that rehabilitation is positively impacted by several protocols such as those performed with intermittent positive pressure [13] or those with neuromuscular electrostimulation [15]. However, these protocols have limitations to the objective evaluation of the findings regarding the gain of muscle strength since the techniques previously proposed are poorly reproduced [8], despite the great diversity of techniques for muscle strength evaluation.…”
Section: Discussionmentioning
confidence: 84%